The Association between Serum Bilirubin Level and Electrochemical Skin Conductance in Chinese Patients with Type 2 Diabetes - Fei Mao; Xiaoming Zhu; Bin Lu; Yiming Li (International Journal of Endocrinology)
Bilirubin is an antioxidant and plays a protective role against cardiovascular and microvascular disease. The aim of this study is to explore the possible protective effect of bilirubin on small nerve function. A total of 265 Chinese patients with type 2 diabetes mellitus (T2DM) were enrolled in the study. Both SUDOSCAN and other traditional diabetic neuropathy examinations including neuropathy symptom score (NSS), the neuropathy disability score (NDS) and Michigan Neuropathy Screening Instrument (MNSI) scores were performed in all patients with T2DM. Blood bilirubin levels were tested in the study. Spearman correlation analysis and multivariate regression analysis were performed to determine the relation between bilirubin level and hands and feet ESC values. Spearman correlation analysis demonstrated a correlation between total bilirubin and ESC levels including hands (r=0.165, P<0.05) and feet (r=0.122, P<0.05) as well as between UCBil and ESC levels including both hands (r=0.172, P<0.05) and feet (r=0.175, P<0.05). Multivariate regression linear analyses showed both total bilirubin and UCBil level were independently associated with hands and feet ESC levels. All these results suggested a positive association between bilirubin level and ESC level, indicating a possible protective role of bilirubin in peripheral small nerve dysfunction of type 2 diabetes mellitus.